Implementation of Earmarking Tax Policy on Motor Vehicle Taxes in Bekasi City - Citra Novlyani (Ilomata International Journal of Tax and Accounting, 2021)
The phenomenon in the research is that there are still many congestion points due to the lack of road construction, lack of infrastructure related to road maintenance, and inadequate transportation modes. This study aims to analyze the Implementation of Earmarking Tax Policy on Vehicle Tax Collection in Bekasi City along with the constraints and efforts in implementation. The theory used in this study is the implementation theory of Ripley and Franklin with 3 indicators of implementation, the level of compliance, smooth routines and functions, and the realization of desired performance and impact. The research method used a qualitative approach with descriptive specificity.The result of the research is the implementation of the Earmarking Tax Policy on the Collection of Motor Vehicle Tax in Bekasi City for the compliance of the implementer in the matter of levying already in accordance with the regulation, but the allocation has not been maximal yet. Functional routine implementers are not yet maximal because there are still few technical issues and separation of funding post / account in the allocation, and no further regulations regarding technical and standard operating procedure (SOP) for earmarking tax funds cannot be seen and controlled. The realization of the performance and the desired impact is also not optimal because there are still many congestion points and road structures that are still not good and adequate public transportation for the entire reach of the City of Bekasi.